FAKTOR-FAKTOR YANG MENENTUKAN AUDIT DELAY - Lidya Primta Surbakti; Ayunita Ajengtiyas Saputri Mashuri (EQUITY, 2015)
This study is performed to examine the effect of Auditor’s Opinion, Solvency Size CPA Firm and profitability toward the probability to Audit Report Lag in Consumer Goods Industry in Indonesian Stock Exchange over period 2010-2012. The population of this research is 35 Consumer Goods Industry companies listed on the Indonesia Stock Exchange over period 2010-2012. The data is obtained based on corporate finance reporting that at publication. It is gained sample amount of 28  ompanies from 35 companies those are classified in Consumer Goods Industry in Indonesian Stock Exchange. The analysis technique used here is multiple linear regression and hypothesis test using t-statistic and F-statistic with level of significance 5%. This research results that  uditor’s Opinion , Size CPA Firm, Solvency and Gain-Loss are not  ignificant effect to Audit Report Lag. We suggest for investors in  ndonesian Stock Exchange that paying attention others factor that  egards Audit Report Lag because with those information theycan make the best decision for their investment..